The Role of Resolvins: EPA and DHA Derivatives Can Be Useful in the Prevention and Treatment of Ischemic Stroke - Tułowiecka, Nikola (Int J Mol Sci, 2020)
Introduction: Most ischemic strokes develop as a result of atherosclerosis, in which inflammation plays a key role. The synthesis cascade of proinflammatory mediators participates in the process induced in the vascular endothelium and platelets. Resolvins are anti-inflammatory mediators originating from eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), which may improve the prognosis related to atherosclerosis by inhibiting the production of proinflammatory cytokines, limiting neutrophil migration, or positively influencing phagocytosis. Although clinical trials with resolvin in humans after stroke have not been realized, they may soon find application. Aim: The aim of the study was to review the available literature on the scope of the possibilities of the prevention and treatment of stroke with the use of resolvins, EPA and DHA derivatives. Materials and methods: The review features articles published until 31 January 2020. The search for adequate literature was conducted using the keywords: stroke and resolvins. Over 150 articles were found. Studies not written in English, letters to the editor, conference abstracts, and duplicate information were excluded. Results: In several studies using the animal model, the supplementation of resolvin D2 decreased brain damage caused by myocardial infarction, and it reversed the neurological dysfunction of the brain. A decrease in the concentration of proinflammatory cytokines, such as TNF-α, Il-6, and Il-1β, was also observed, as well as a decrease in the scope of brain damage. In the context of stroke in animals, the treatment with resolvin D2 (RvD2) (injection) has a better effect than supplementation with DHA. Conclusions: Resolvins are characterised by strong anti-inflammatory properties. Resolvins improve prognosis and decrease the risk of developing cardiovascular disease, consequently lowering the risk of stroke, and may find application in the treatment of stroke.